Introduction to the Hebrew Bible. The Deuteronomistic history - Collins, John J. (John Joseph), 1946- (Fortress Press, 2018)
John J. Collins's popular Introduction to the Hebrew Bible has now been divided into four volumes, one for each major part of the Hebrew Bible. This volume focuses on the Deuteronomistic History. Here, Collins explores the books of Joshua through 2 Kings, the main account of Israel's history. This volume, based on the new third edition of the Collins textbook, is presented in a new and engaging format with new maps and images. An index has been added to the volume for the first time.